CONTRIBUTION TO THE STUDY OF ASSESSING RAINFALL PATTERNS AS INDICATORS OF CLIMATE CHANGE: A STUDY IN KINSHASA CITY, DEMOCRATIC REPUBLIC OF CONGO - Rais Seki Lenzo; Jean-Pierre Kalay Kut; Kasongo Numbi Kashemukunda; Kaloucha Kanga Nsiama; Gradi Kalonji Lelo; Ange Kra; Aurelie Nkayulu Wa Luvuvamu; Kevin Lumpungu Lutumba (Geological Behavior)
Climate change is manifesting globally with phenomena like floods, storms, crop failures, droughts, and migrations. Kinshasa, the capital of the Democratic Republic of Congo (DRC), is significantly impacted by these changes. Despite its vulnerability, modern research on climate change in the region is lacking. This study aims to fill this gap by investigating rainfall data as an indicator of climate change in Kinshasa. Analyzing 32 years of daily rainfall records (1988-2019), it evaluates patterns such as consecutive dry days, rainy season duration, and maximum daily rainfall. This comprehensive assessment seeks to enhance understanding of climate dynamics in Kinshasa and support the development of targeted resilience measures in the DRC